Outcomes of Take-Back Operations in Breast Reconstruction with Free Lower Abdominal Flaps - Yim, Ji Hong; Yun, Jiyoung; Lee, Taik Jong; Kim, Eun Key; Cho, Jonghan; Eom, Jin Sup (Archives of Plastic Surgery, 2015)
Background Microvascular complications after free-flap breast reconstructions are potentially devastating problems that can increase patient morbidity and lead to flap loss. To date, no comprehensive study has examined the rates of salvage and the methods of microvascular revision in breast reconstruction. We reviewed the treatment of microvascular complications of free-flap breast reconstruction procedures over a seven-year period.Methods A retrospective review of all patients who underwent microvascular breast reconstruction at our institution between April 2006 and December 2013 was conducted. Based on their surgical records, all patients who required emergency re-exploration were identified, the rate of flap salvage was determined, the factors associated with flap salvage were evaluated, and the causes and methods of revision were reviewed.Results During the review period, 605 breast reconstruction procedures with a free lower abdominal flap were performed. Seventeen of these flaps were compromised by microvascular complications, and three flaps were lost. The overall salvage rate was 82.35%. No significant differences between the salvaged group and the failed group were observed with regard to age, BMI, axillary dissection, number of anastomotic arteries and veins, recipient vessel types, or use of the superficial inferior epigastric vein in the revision operation. Successful salvage of the flap was associated with a shorter time period between recognizing the signs of flap compromise and the take-back operation.Conclusions The salvage rate of compromised lower abdominal flaps was high enough to warrant attempting re-exploration. Immediate intervention after the onset of flap compromise signs is as important as vigilant postoperative monitoring.
Keywords: Perforator flap; Surgical flaps; Free tissue flaps; Salvage therapy; Breast